Advances and retreats: the issue of permanence and success in the context of the Technical Course in Informatics Integrated to High School at IFNMG – Campus Montes Claros (Research, Society and Development, 2021)
Integrated High School is a new modality of education offered in the Brazilian context by the Federal Institutes of Education, Science and Technology. This modality seeks to train man in its integrality, because it integrates knowledge produced socially both in the area of general/scientific training and in the professional/technological area. In this sense, the present work seeks to address the theme of Integrated High School, focusing on the Technical Course in Informatics Integrated to High School at IFNMG/Campus Montes Claros. This is a bibliographic and documentary research, presenting as the central objective to carry out the survey of the indexes of conclusions of the entry classes in the years 2012 to 2017. In addition, it seeks to contextualize the permanence and success of students in the field of professional education and the course under investigation, presenting the actions to promote permanence and success. From the data collection, it was found that the first class of the course presented the lowest completion rate when compared to the other classes, and the subsequent ones presented better results. However, there was no progressivity in the results, there are, in some situations indentation in completion indexes. In view of results such as this, IFNMG elaborated the Institutional Strategic Plan of Permanence and Success with a view to improving both the teaching-learning process and the consequent increase in indicators related to the school success of its student body.